2021
DOI: 10.1002/bco2.114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of advanced glycation end products on nocturia or sleep disorders: A longitudinal study

Abstract: Objective: This study aimed to investigate the effect of advanced glycation end products (AGEs) on nocturia and sleep disorders in community-dwelling adults. Materials and Methods: This longitudinal study evaluated AGEs level, sleep disorders and nocturia frequency in 447 community-dwelling adults between May 2011 and May 2016. Sleep disorders were evaluated using the Pittsburgh Sleep Quality Index (PSQI) score. Participants were divided into two groups: AGEs-low (≤1.80) and AGEs-high (>1.80). The longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Matsumoto et al showed in a cross-sectional study of 1113 adults that the amount of advanced glycation end products (AGEs) measured by skin autofluorescence, surrogate markers of oxidative stress, were significantly associated with the frequency of nocturia [ 33 ]. Konishi et al found oxidative stress to be significantly associated with worsening sleep disorders, although not with worsening nocturia frequency [ 34 ]. It is known that NE and nocturia share common pathophysiology pathways [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al showed in a cross-sectional study of 1113 adults that the amount of advanced glycation end products (AGEs) measured by skin autofluorescence, surrogate markers of oxidative stress, were significantly associated with the frequency of nocturia [ 33 ]. Konishi et al found oxidative stress to be significantly associated with worsening sleep disorders, although not with worsening nocturia frequency [ 34 ]. It is known that NE and nocturia share common pathophysiology pathways [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Switching to the field of functional urology, the paper by Konishi et al 7 investigated the effect of advanced glycation end products (AGEs) on nocturia and sleep disorders. The key background information includes the known associations between sleep disturbances and nocturia and adds emerging information on oxidative stress imbalance as a relation to nocturia.…”
Section: Figurementioning
confidence: 99%